2003
DOI: 10.1128/aac.47.3.1037-1046.2003
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Residues of Escherichia coli DNA Gyrase Required in Coupling ATP Hydrolysis to DNA Supercoiling and Amino Acid Substitutions Leading to Novobiocin Resistance

Abstract: DNA gyrase is a bacterial type II topoisomerase which couples the free energy of ATP hydrolysis to the introduction of negative supercoils into DNA. Amino acids in proximity to bound nonhydrolyzable ATP analog (AMP ⅐ PNP) or novobiocin in the gyrase B (GyrB) subunit crystal structures were examined for their roles in enzyme function and novobiocin resistance by site-directed mutagenesis. Purified Escherichia coli GyrB mutant proteins were complexed with the gyrase A subunit to form the functional A 2 B 2 gyras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 49 publications
2
90
0
Order By: Relevance
“…1E). It is not clear why this may be, although higher mistranslation would also result in alteration of an asparagine critical for gyrase function (34), which may offset any advantages from resistant variants of the protein.…”
Section: Discussionmentioning
confidence: 86%
“…1E). It is not clear why this may be, although higher mistranslation would also result in alteration of an asparagine critical for gyrase function (34), which may offset any advantages from resistant variants of the protein.…”
Section: Discussionmentioning
confidence: 86%
“…6971) (Soussy et al, 1993), which carries a temperaturesensitive gyrA mutation, and with strain N4177 [F ÿ gyrB203(ts) strA galK gyrB221(cou R )] (E. coli Genetic Stock Center no. 6462) (Gross et al, 2003), which carries a temperature-sensitive gyrB mutation. The NbGyrA and NbGyrB cDNA fragments encoding the full-length NbGyrA and NbGyrB proteins but lacking the N-terminal extensions were cloned into the pBAD18 vector to generate pBAD-NbGyrA and pBAD-NbGyrB.…”
Section: Complementation Of Escherichia Coli Gyra and Gyrb Mutantsmentioning
confidence: 99%
“…To examine the functional similarities between plant DNA gyrase subunits and their bacterial counterparts, complementation analysis was performed with E. coli strains KNK452 (Soussy et al, 1993) and N4177 (Gross et al, 2003), which carry a temperature-sensitive gyrA and gyrB mutation, respectively (Figure 1). The cDNA fragments encoding the NbGyrA and NbGyrB proteins without the N-terminal extensions were cloned into pBAD18 (Blanc-Potard and Bossi, 1994) such that expression of NbGyrA and NbGyrB was under the control of the arabinose-dependent promoter.…”
Section: N Benthamiana Homologs Of the Dna Gyrase A And B Subunitsmentioning
confidence: 99%
“…to asparagine while the re-conversion of asparagine to aspartate on this location restored both ATPase and DNA supercoiling activities wet experiments [9]. This emphasizes the extreme relevance of Asp-73 residue for catalytic activity of DNA gyrase.…”
Section: Resultsmentioning
confidence: 56%
“…The study revealed DNA gyrase as a potential target for the antimicrobial compounds. The protein, DNA gyrase, is a unique protein that is involved in coupling the free energy of ATP hydrolysis to formation of negative supercoils into DNA [9]. The protein has emerged as a clinical target for antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%